Post-Weaning Feed Intake and Performance of Bulls Developed in an Automated Feed Intake Management System - Brandon J. Fraser; J. W. L. Banks; Karol E. Fike; Jason M. Warner (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: Our objectives were to compare expected and observed dry matter intake (DMI) and average daily gain (ADG) of beef bull calves fed in an automated feed intake system using modeled nutrient requirement equations. Study Description: Feed intake and performance data from purebred Angus, Hereford, and Simmental bull calves across three calf crops (birth years 2021 [n = 40], 2022 [n = 37], and 2023 [n = 41]) were utilized for this analysis. Projected DMI and ADG were calculated for each group of bulls by year on an individual basis using the Growing Bull module of the Excel-based Beef Ration and Nutrition Decision Software (BRaNDS) formulation program. These predicted figures were compared to the Insentec intake data and analyzed via SAS. The Bottom Line: While significant individual variation in intake exists, the BRaNDS program more accurately predicts DMI than ADG for growing bulls. The model consistently underestimated actual ADG, highlighting the need for refinement in predicting growth outcomes, even though its predictions for intake aligned reasonably well with observed values.
Keywords: bulls; feed intake; performance